Trends in precision diagnosis and monitoring of inflammatory bowel diseases: the potential of proteomic and metabolomic biomarkers - S. V. Lyamina; I. V. Maev; T. I. Ivanova; E. O. Kozhevnikova; S. V. Kalish (Бюллетень сибирской медицины, 2025)
Omics technologies, including proteomics and metabolomics approaches, provide promising opportunities to improve the accuracy of diagnosis and monitoring of the course of inflammatory bowel disease (IBD). Integration of these advanced research areas into clinical medicine not only allows for a more in-depth assessment of the pathogenesis of IBD, but also opens avenues for innovative therapeutic strategies adapted to individual patient profiles and patient cohorts.The lecture analyzes trends in the identification of biomarkers with high sensitivity and specificity that can be used both for diagnosis and prognosis of the course of IBD subtypes, and for predicting the response to therapy, which, ultimately, will contribute not only to improved treatment outcomes, but also to an increase in the quality of life of patients.The authors conducted a non-systematic, descriptive review of the literature with a search depth of 10 years, aimed at systematizing data on the achievements of proteomics and metabolomics approaches for the diagnosis, monitoring of the IBD course, and personalization of therapeutic strategies. The search for literary references was carried out using Scopus, Web of Science, MedLine, the Cochrane Library, EMBASE, Global Health, CyberLeninka, and RSCI databases.The analysis of the results of experimental and clinical studies allowed to identify a number of biomarkers – candidates for testing and potential implementation in routine clinical practice. Convincing data were obtained on the potential benefits of integrating proteomics and metabolomics studies with other omics approaches. The importance of an interdisciplinary approach combining the results of clinical studies with modern approaches in bioinformatics and molecular biology for the development of more effective diagnostic tools and strategies is obvious.